Tuning of the para-position of pyridyl ligands impacts the electrical properties of a series of Cd(ii) ladder polymers. Issue 30 (2nd July 2019) - Dutta, Basudeb; Dey, Arka; Sinha, Chittaranjan; Ray, Partha Pratim; Mir, Mohammad Hedayetullah
Abstract : This work describes the tuning of electrical nature of three Cd(ii )-based 1D coordination polymers by the modifications of para -substituent of pyridyl ligands. Abstract : Herein, we report the synthesis, structural characterization and electrical conductivity of three new one-dimensional coordination polymers (1D CPs), [Cd(nip)(4-Clpy)(CH3 OH)] (1 ), [Cd(nip)(4-Brpy)(CH3 OH)] (2 ) and [Cd(nip)(4-Phpy)(H2 O)]·DMF·3H2 O (3 ) (H2 nip = 5-nitroisophthalic acid, 4-Clpy = 4-chloropyridine, 4-Brpy = 4-bromopyridine, 4-Phpy = 4-phenylpyridine and DMF = N, N -dimethylformamide). The conductivity of the compounds was successfully tuned via the modification of the para -position of the 4-Xpy (X = Cl, Br and Ph) ligands. The electrical analysis indicated that compound3 has the highest conductivity (22.25 × 10 −4 S m −1 ) under illumination followed by2 (19.38 × 10 −4 S m −1 ) and1 (12.68 × 10 −4 S m −1 ). The optical characterization and density functional theory (DFT) computation also support the observed progression of conductivity in the materials. Here, the highest conductivity of compound3 is attributed to the better π⋯π stacking interactions among the 4-Phpy and nip ligands, and the consequently increased charge transport between adjacent chains.